2010
DOI: 10.1097/dbp.0b013e3181d7b1d3
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Risk and Psychiatric Outcome in Adolescents Born Preterm With Very Low Birth Weight or Term Small for Gestational Age

Abstract: Lower birth weight, shorter gestation, and intraventricular hemorrhage were risk factors for psychiatric problems in the very low birth weight group. Lower Apgar score increased the risk for autism spectrum symptoms and internalizing symptoms. Among adolescents born term small for GA, the main risk factor for psychiatric symptoms was low socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 31 publications
8
73
2
8
Order By: Relevance
“…For example, a Norwegian study examined psychiatric outcomes in adolescents born preterm and VLBW and reported that LBW was associated with reduced psychosocial function and an increase in ADHD symptoms [27]. Similar to other epidemiological studies, these findings were significant after adjusting for confounding factors, including maternal mental illness, gender, and social economic status.…”
Section: Figuresupporting
confidence: 66%
“…For example, a Norwegian study examined psychiatric outcomes in adolescents born preterm and VLBW and reported that LBW was associated with reduced psychosocial function and an increase in ADHD symptoms [27]. Similar to other epidemiological studies, these findings were significant after adjusting for confounding factors, including maternal mental illness, gender, and social economic status.…”
Section: Figuresupporting
confidence: 66%
“…Our findings are also in line with the previous studies showing more ASD symptoms or traits in children and adolescents born preterm. 12,21,24 Interestingly, and against our hypothesis, the VLBW group reported 0.3 SD units lower levels of exceptional attention to detail than those who were term-born. We also hypothesized that higher levels of ASD-related traits would be most characteristic of the VLBW young adults who were born SGA.…”
Section: Discussionmentioning
confidence: 65%
“…23 In comparison with relatively rare categorical diagnoses, assessing ASD-related traits as dimensions offers more detailed information on these behaviors, not only among those who have ASD, but across the whole population. In the few existing studies, children born at ,26 weeks of gestation were parent-and teacher-rated 21 and VLBW adolescents were self-and parent-rated 12,24 as having more ASD-related traits than term-born peers. It remains unknown if the effects of preterm birth on ASD-related traits persist into adulthood.…”
mentioning
confidence: 99%
“…[13] Differences in population denominators can result in wide variation in outcomes, and the study of birth weight-defined cohorts may confound results with the inclusion of babies born small for gestational age (SGA), which may be associated with different behavioural outcomes. [14,15] Different assessment tools and ages at assessment can also result in varying prevalence estimates for both symptoms and disorders, especially in the case of mental health assessments. In particular, the use of self-report versus informant ratings can produce widely different outcomes.…”
Section: Methodological Considerationsmentioning
confidence: 99%